Physicochemical and Biological Characterization of Pep‐1/Elastin Complexes. (23rd July 2013) - Ahmad Nasrollahi, Saman; Taghibiglou, Changiz; Fouladdel, Shamileh; Dinarvand, Rasoul; Moosavi Movahedi, Ali A.; Azizi, Ebrahim; Farboud, Effat S.
Abstract : Transdermal drug delivery of proteins is challenging because the skin acts as a natural and protective barrier. Several techniques including using the cell‐penetrating peptides have been studied to increase the penetration of therapeutic proteins into and through the skin. Cell‐penetrating peptides facilitate and improve the transduction of large and hydrophilic cargo molecules through plasma membrane. We have recently reported an efficient skin delivery of elastin protein in complex with a cell‐penetrating peptide called Pep‐1. As the biophysical characteristics of cell‐penetrating peptide/protein complexes have been linked with their biological responses, in this study, we investigated biophysical properties of Pep‐1/elastin complexes (ratio 10:1) stored in three temperatures (−20 °C, 4 °C and 25 °C) by photon correlation spectroscopy, circular dichroism and isothermal denaturation. We also evaluated the ability of transduction of this complex into cells and skin tissue using both fluorescence microscopy and Kodak In‐Vivo FX Pro Imaging System. Abstract : Our results reveal that Pep‐1/elastin complex in appropriate ratio can not only transduce into cultured cells but also penetrate the living animal cells, that introducing high efficiency and effectiveness of cell‐penetrating peptide/protein complexes.